Evaluation of peroxisome proliferator‐activated receptor agonists on interleukin‐5‐induced eosinophil differentiation. Issue 3 (July 2014) - Smith, Steven G.; Hill, Mike; Oliveria, John‐Paul; Watson, Brittany M.; Baatjes, Adrian J.; Dua, Benny; Howie, Karen; Campbell, Heather; Watson, Rick M.; Sehmi, Roma; Gauvreau, Gail M.
Summary Peroxisome proliferator‐activated receptor (PPAR) agonists have been suggested as novel therapeutics for the treatment of inflammatory lung disease, such as allergic asthma. Treatment with PPAR agonists has been shown to inhibit airway eosinophilia in murine models of allergic asthma, which can occur through several mechanisms including attenuated generation of chemoattractants (e.g. eotaxin) and decreased eosinophil migrational responses. In addition, studies report that PPAR agonists can inhibit the differentiation of several cell types. To date, no studies have examined the effects of PPAR agonists on interleukin‐5 (IL‐5) ‐induced eosinophil differentiation from haemopoietic progenitor cells. Non‐adherent mononuclear cells or CD34+ cells isolated from the peripheral blood of allergic subjects were grown for 2 weeks in Methocult® cultures with IL‐5 (10 ng/ml) and IL‐3 (25 ng/ml) in the presence of 1–1000 nm PPARα agonist (GW9578), PPARβ/δ agonist (GW501516), PPARγ agonist (rosiglitazone) or diluent. The number of eosinophil/basophil colony‐forming units (Eo/B CFU) was quantified by light microscopy. The signalling mechanism involved was assessed by phosphoflow. Blood‐extracted CD34+ cells cultured with IL‐5 or IL‐5 + IL‐3 formed Eo/B CFU, which were significantly inhibited by rosiglitazone (100 nm, P < 0·01) but not GW9578 or GW501516. In addition, rosglitazone significantly inhibited IL‐5‐induced phosphorylation of extracellular signal‐regulated kinase 1/2. We observed an inhibitory effect of rosiglitazone on eosinophil differentiation in vitro, mediated by attenuation of the extracellular signal‐regulated kinase 1/2 signalling pathway. These findings indicate that the PPARγ agonist can attenuate tissue eosinophilia by interfering with local differentiative responses.